HRD in perspective - Nadler, Leonard (1994)
Human resources development has become an important field with the area of human resources and organization behavior. We need to continue to explore how HRD works in conjunction with other fields, so that they can all contribute to the goals and missions of organizations, while keeping in mind that the focus is on people.